UJI AKTIVITAS ANTIOKSIDAN KANDUNGAN FITOKIMIA JUS BUAH GANDARIA (Bouea macrophylla Griffith) - Lolaen, Landy A. Ch; Fatimawali, Fatimawali; Citraningtyas, Gayatri (UNIVERSITAS SAM RATULANGI, 2013)
The accomplishment of this research was to knowing the fito-chemical composition ofGandaria fruit’s juice and its potential as anti-oxidant. The Gandaria fruit’s juice were madeusing the blender device then filtered by filtration paper for extraction of the juice.Determination of fito-chemical is done with color reaction test for identification of alkaloid,fenolik, flavonoid, saponin, steroid and terpenoid. The anti-oxidant test were using freeradicalscavengers DPPH (1,1-difenil-2-pikrilhidrazil) and recorded with Spectrophotometerat 515nm wave length. Result of the research indicates that in Gandaria fruit’s juice has beendetected with saponin and fenolik fito-chemicals. The Gandaria fruit’s juice has the antioxidantactivity in IC50 of 36,4 mg/ml. The verdict and conclusion for the research is,Gandaria fruit’s juice has the composition of fito-chemical (saponin and fenolik) which isvery potential as anti-oxidant.Keywords : Gandaria fruit’s juice, anti-oxidant, DPPH, fito-chemical composition